REPAIR OF CEMENT, GRAIN, MINERAL WAGONS AND GONDOLA CARS IN A SINGLE FLEXIBLE ASYNCHRONOUS FLOW (Transport systems and technologies, 2022)
The publication updates the issue of wagon repair in modern conditions and highlights the main problems associated with the method of organization of work. Low productivity is due to outdatedequipment and worn-out rolling stock, poor training of staff involved. The article contains the main provisions of changing the method of repair, calculating the possibility of loading productionpositions, calculating the program of repairing wagons, determining the number of ways of their routes, analyzing the shortcomings of flexible asynchronous flow, developing solutions for testingflexible flow in computer simulations. Summarizing this material provides an opportunity to consider and develop a project based on the Stryi Wagon Repair Plant for flexible flow or its modification toincrease repair capacity. The article calculates the time of repair of wagons by the flow method and using a flexible asynchronous multichannel method of repair, the graphs show the difference indowntime between the same types of wagons and the type of repair, provided that they are taken in the same condition before repair work. From these calculations, it can be concluded that the streamlinedmethod of repair has exhausted all its resource potential, and will continue to incur the cost of paying employees, maintenance of equipment and other costs associated with production.
Keywords: Flexible asynchronous flow, overhaul, depot repair, wagon repair method.